2019
DOI: 10.1016/j.chemosphere.2019.05.179
|View full text |Cite
|
Sign up to set email alerts
|

The fungicide mancozeb affects soil invertebrates in two subtropical Brazilian soils

Abstract: h i g h l i g h t s Mancozeb offer a risk to key-groups of non-target species in subtropical soils. F. candida and E. crypticus were the most sensitive speciesto Mancozeb. Tests with earthworms were insufficient to protect other non-target invertebrates populations. A multicriteria approach (soil types and organisms) is needed for pesticides risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
1
13
0
4
Order By: Relevance
“…Only one reported NOEC mortality value for H. aculeifer was comparable to that of the nematodes (1.05 mg a.i./kg dry soil [EFSA, 2020]). A study in tropical soils showed that mancozeb toxicity can vary with the type of soil (Camargo Carniel et al, 2019). Whereas the toxicity test with collembolans in Oxisol soil revealed comparable effect concentrations with the nematodes in the present study (EC50, LOEC, NOEC: 2.7, 2, <2 mg a.i./kg dry soil, respectively), almost no effects could be found in Ultisol soil (EC50, LOEC, NOEC: 100, 1000, >100, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one reported NOEC mortality value for H. aculeifer was comparable to that of the nematodes (1.05 mg a.i./kg dry soil [EFSA, 2020]). A study in tropical soils showed that mancozeb toxicity can vary with the type of soil (Camargo Carniel et al, 2019). Whereas the toxicity test with collembolans in Oxisol soil revealed comparable effect concentrations with the nematodes in the present study (EC50, LOEC, NOEC: 2.7, 2, <2 mg a.i./kg dry soil, respectively), almost no effects could be found in Ultisol soil (EC50, LOEC, NOEC: 100, 1000, >100, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In a field experiment, soil nematodes responded with a slight increase of densities after 90 days of exposure to mancozeb (as Dithane M‐45) at 10‐fold higher doses than recommended by the manufacturer (0.96 g a.i./m 2 ; assuming a mixing depth of 5 cm and a soil density of 1.5 g/cm 3 [Camargo Carniel et al, 2019], this corresponds to a nominal concentration of 13 mg a.i./kg dry soil; Petz & Foissner, 1989). In the present study, mancozeb (nonsignificantly) increased nematode densities at considerably higher nominal concentrations (≥89 mg a.i./kg dry soil, corresponding to real exposure concentrations of 8–11 mg a.i./kg dry soil).…”
Section: Resultsmentioning
confidence: 99%
“…The indirect effect of the use of fungicides on the populations of springtails can be attributed to the elimination of many fungi, which serve as food for several species of springtails (Scheu & Folger, 2004;Sawahata, 2006). In addition, Carniel et al (2019), found that the application of the fungicide Mancozebe® reduces the survival and reproduction of springtails.…”
Section: Resultsmentioning
confidence: 99%
“…The phytosanitary products applied to the crop predecessor to soybean in the 2019/2020 harvest are shown in Table 2. The specific details regarding the applied phytosanitary products are necessary, as many of these products can reduce the populations of springtails (Frampton & Wratten, 2000;Carniel et al, 2019).…”
Section: Crop Managements Conducted During 2019 and 2020mentioning
confidence: 99%
“…Contudo, apesar de estar localizado em uma das regiões do país com maior disponibilidade de informações sobre qualidade da água de consumo humano (Barbosa et al, 2015;Oliveira et al, 2019), o Espírito Santo, apresenta um baixo número de municípios com dados para agrotóxicos e carências para operacionalização do sistema (Altoé, 2018 (Brasil, 2005(Brasil, , 2008(Brasil, , 2017 , 2020), mostra ligação a quedas na resposta imune de mexilhões a proliferação de patógenos oportunistas (Iori et al, 2019), e a distúrbios metabólicos em peixes após longa exposição (Li et al, 2017). O fungicida mancozebe, também amplamente consumido no Brasil, demostrou potencial de interferência na reprodução e desenvolvimento de invertebrados em solos brasileiros (Carniel et al, 2019) e também no sistema reprodutivo feminino em mamíferos, através de danos nas células granulosas do ovário (Paro et al, 2012). Lopez-Antia et al, 2018) encontraram evidências de que a ingestão de alimentos contaminados pelo fungicida flutriafol podem reduzir em até 50 % o tamanho da prole de algumas aves.…”
Section: Agrotóxicos Associados As Culturasunclassified